Photoluminescence and photonic absorbance of Ce2(MoO4)3 nanocrystal synthesized by microwave–hydrothermal/solvothermal method - Wachiraporn Maisang (2018)
© 2016 The Nonferrous Metals Society of China and Springer-Verlag Berlin Heidelberg In this research, cerium (III) nitrate hexahydrate (Ce(NO3)3·6H2O) and ammonium molybdate tetrahydrate ((NH4)6Mo7O24·4H2O) with Ce3+-to-Mo6+ molar ratio of 2:3 were dissolved in 40 ml different solvents of deionized (DI) water, polyethylene glycol (PEG) and ethylene glycol (EG) to form different solutions which were followed by adjusting pH from the traditional values to 7.0 and 10.0 with 1 mol·L−1 sodium hydroxide (NaOH). Subsequently, the solutions were processed by 270-W microwave–hydrothermal/solvothermal method. Phase, morphology, vibrational modes and photonic properties were fully characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), Raman spectrophotometry, ultraviolet–visible (UV–Vis) absorption and photoluminescence (PL) spectroscopy. The as-synthesized products were pure cerium molybdenum oxide (Ce2(MoO4)3) of nanoparticles clustered together as nanoplates in DI water and PEG solvents, and of spindle-like nanoparticles in EG solvent, including the presence of Ce–O–H mode and MoO4 units. The results show that direct energy gaps of the first two have the same value of 2.30 eV, and that of the last is 2.80 eV, including their blue emission at the same wavelength of 488 nm.